Liquefaction analysis of sandy soil during strong earthquake in Northern Thailand - Sukkarak, Raksiri; Tanapalungkorn, Weeradetch; Likitlersuang, Suched; Ueda, Kyohei (Soils and foundations, 2021)
Northern Thailand has experienced several earthquakes which led to soil liquefaction in the past few decades. Traditional methods of evaluating liquefaction potential involve standard penetration test (SPT) or cone penetration tests. This research augmented experimental results with numerical methods to evaluate the liquefaction potential of Mae Lao Sand in Chiang Rai province of northern Thailand. SPT and downhole seismic test data collected during a field investigation at the Mae Lao site were compared to a 1D site response model analysis of the site. A series of undrained monotonic and cyclic triaxial tests was conducted on Mae Lao Sand specimens with different initial void ratios and confining pressures. Cyclic triaxial test results with varying deviator stress amplitudes were used to draw liquefaction resistance curves. Results from numerical simulation of sand liquefaction were used to characterise the stress–strain-pore water pressure response of Mae Lao Sand. 1D site response analysis determined seismic responses with different geological and groundwater conditions. All put together, the results showed that pore water pressure ratio decreases with increasing sand stiffness, the thickness of a soil layer significantly increases its liquefaction potential, and in-situ conditions and groundwater depths have major influences on the liquefaction potential of sand layers.